Historia dyscypliny pedagogiki na Uniwersytecie Poznańskim oraz Uniwersytecie im. Adama Mickiewicza w Poznaniu w stulecie istnienia – próba rekonstrukcji - Nowak-Kluczyński, Konrad (Studia Edukacyjne, 2020)
The article is an attempt to chronologically reconstruct the history of pedagogy at Academia in Poznań, present it according to themes and considering the changes in organization structure and the historical context. It recognizes Poznań academic pedagogy as a scientific discipline on the basis of an administrative and institutional framework, both areas influencing each other directly. The changes in the structure of particular organizational units have been conditioned by the development of pedagogy as a science, and vice versa.